Recurrent in-stent restenosis with total occlusion remedied with drug-eluting balloon angioplasty - Mohd Shah, Azarisman Shah; Zulkifli , Mahmood Sabruddin; Mohd Ali, Rosli (University of Tokyo * Graduate School of Medicine, 2011)
We report a 69 year old female who presented with chest pain to the Emergency Department of the National Heart Institute Malaysia. Her history revealed that she had had 2 separate episodes of chest pain beginning in 2002, resulting in total occlusion of her mid left anterior descending artery (LAD) requiring percutaneous coronary intervention and stenting on both occasions. Cine angiogram on her current admission revealed recurrent target lesion in-stent restenosis with total occlusion of the distal LAD. Intravascular ultrasound revealed multilayered suboptimally deployed stents in the LAD. Successive drug-eluting balloon deployments resulted in sustained patency of the LAD after 1 year.